Cyclophotocoagulation versus Ahmed Glaucoma Implant in Neovascular Glaucoma with Poor Vision at Presentation - Alabduljabbar K; Bamefleh DA; Alzaben KA; Al Owaifeer AM; Malik R (Clinical Ophthalmology, 2024)
Khaled Alabduljabbar,1 Dania A Bamefleh,2 Khawlah Adel Alzaben,1 Adi M Al Owaifeer,2,3 Rizwan Malik4 1Fellowship and Residency Training Program, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2Glaucoma Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 3Ophthalmology Unit, Department of Surgery, College of Medicine, King Faisal University, Al-Ahsa, Saudi Arabia; 4Department of Surgery, Sheikh Khalifa Hospital, Abu Dhabi, United Arab EmiratesCorrespondence: Khaled Alabduljabbar, Fellowship and Residency Training Program, King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia, Email kalabduljabbar@gmail.comPurpose: To evaluate the outcomes of surgical intervention in eyes with neovascular glaucoma (NVG) and poor vision, comparing the Ahmed glaucoma implant with cyclophotocoagulation (CPC).Patients and Methods: This study is a double-armed cohort retrospective review of medical records of patients with NVG who had a visual acuity of 20/200 or less and underwent one of the two procedures as a primary intervention: Ahmed glaucoma valve (AGV) or cyclophotocoagulation (CPC). The study was conducted at King Khaled Eye Specialist Hospital in Riyadh, Saudi Arabia, from January 2014 to June 2019, with a total study period of 1 year. The main outcome measures included the surgical success rate, changes in intraocular pressure (IOP), the number of antiglaucoma medications, corrected distance visual acuity, and the reoperation rate for glaucoma.Results: The preoperative IOP was 40.4 ± 10.6 mmHg (Median 40) in the CPC group and 39.4 ± 10.2 mmHg (Median 40) in the AGV group (P = 0.6). At 1 year, the IOP ranged from 12.5 to 28 mmHg (Median 18) in the CPC group and 14 to 21.5 mmHg (Median 17) in the AGV group (P = 0.016). Survival analysis showed a 51% success rate in the CPC group and an 89% success rate at 1 year in the AGV group (p> 0.0001).Conclusion: CPC and AGV procedures yielded good outcomes with similar IOP levels 12 months after the surgery. However, AGV demonstrated a higher overall success rate and a lower medication requirement than CPC.Keywords: neovascular glaucoma, NVG, Ahmed glaucoma valve, Ahmed glaucoma implant, cyclophotocoagulation